G65(P) Neuropsychiatric presentation of antibody negative limbic encephalitis. (27th April 2015) - Moodley, K; Menounou, A; Kirby, A; Durso, A; Krishnakumar, D
Abstract : Autoimmune encephalitis is an increasingly recognised cause for a combination of symptoms of seizures, disturbance of memory, behaviour and cognition. Other manifestations include acute onset movement disorders, unexplained encephalopathy and refractory status epilepticus. N-methyl aspartate (NMDA) encephalitis and voltage gated potassium channel mediated (VGKC) limbic encephalitis are the two commonest causes of autoimmune encephalitis. These children initially present to general paediatricians therefore it is vital to consider this in the differential diagnosis of infective encephalitis as prompt recognition, investigation and immune therapy determines longterm outcome. Early recognition and treatment can potentially halt temporal lobe atrophy and improve outcome. We report a 14 year old girl who presented with symptomatic, intermittent memory loss, behaviour disturbance, fatigue and cognitive change with limbic encephalitis. Initial investigations revealed negative PCR for HSV, EBV. Brain imaging detected mesial right temporal high signal area in FLAIR sequences. EEG showed epileptic inter-ictal focal abnormality over right frontal mesial temporal region. NMDA, VGKC, Anti GAD, Hu, Ma, CV2, CRMP5 and thyroid antibodies were negative. Screening for tumour with baseline abdominal ultrasound and CXR were negative. Baseline WISC testing prior to starting medications revealed her immediate memory for verbal information was in the low average range (verbal immediate index score:82, 12th percentile) and her time delayed recall verbal information was in the impaired range (verbal delayed index score:72, 3rd percentile). She was treated with iv methylprednisolone followed by tapering dose of oral prednisolone. Repeat WISC assessment is due in 6 months. Limbic encephalitis should be considered in children with prominent neuropsychiatric manifestation of encephalitis. Her future MRI reports will determine the 3 month and 6 month outcome for this teenager. Longterm surveillance for tumour detection is recommended in autoimmune encephalitis.